(untitled) (TAJ: Journal of Teachers Association, 2009)
Transabdominal sonography (TAS) and Transvaginal sonography (TVS) were compared for follicular monitoring in 62 patients of infertility. These patients were referred for follicular monitoring in normal and stimulated cycles from infertility clinic. Patients’ compliance and acceptance was excellent for TVS technique as compared to TAS technique. The overall resolution of ovarian and follicular anatomy was much better in TVS. With TAS only 25.5% had good visualization of follicles as compared to 84.8% (p<0.05) in TVS. TVS offered advantage of much better detection rate of smaller follicles (< 10 mm) and higher accuracy in assessing number of follicles. doi: 10.3329/taj.v21i1.3215 TAJ 2008; 21(1): 31-34